An Extremum-Preserving Iterative Procedure for the Imperfect Interface Problem (Communications in Computational Physics, 2018)
In this paper we propose an extremum-preserving iterative procedure forthe imperfect interface problem. This method is based on domain decompositionmethod. First we divide the domain into two sub-domains by the interface, thenwe alternately solve the sub-domain problems with Robin boundary condition. Weprove that the iterative method is convergent and the iterative procedure is extremum-preservingat PDE level. At last, some numerical tests are carried out to demonstratethe convergence of the iterative method by using a special discrete method introducedon sub-domains.